Assessment of International Partnerships in Educational Institutions and their Intricacies: A Brief Study - Maria Kaguhangire-Barifaijo; Rose B. Namara (Research Highlights in Language, Literature and Education Vol. 1, 2022)
This chapter highlights the benefits as well as challenges in international partnerships emerging from local and international literature and based on the experience of the authors with an international partnership that has failed in with recommendations on the way forward . In reaction to the effects of globalization and changes on the world, international partnerships have developed into an interactive response. Higher education institutions now form alliances to compete for resources, students, researchers, and academic programmes. These cooperation activities are thought to improve academic programme quality, institutional profiling, capacity building, potential for research capability, and the impact of research on policy and practice across a range of contexts. While it seems clear that international partnerships are inevitable, intricacies in agreements and deep inequalities undergird many of the current trends in these partnerships. Authors adopted the “Critical Theory Approach” to explain the inherent inequalities which affect harmony, cohesion, success and sustainable relationships. In this essay, it is claimed that while international partnerships are still essential for developing institutional capacity, they are nonetheless hampered by unequal power relations and are often dominated by the more powerful partners. The paper concludes that lack of clear agreements have an impact on the sustainability of partnerships. Hence, institutions need to be vigilant to negotiate the powers that enhance harmony through formal and transparent agreements and bring everyone on board to avoid institutional conflicts. This paper elicits a sustainable dialogue on the nature of partnerships. The study attempted to reflect on the current practices in order to come to a better understanding of the unique nature of this collaboration.